Effect of Saccharomyces cerevisiae (Yea Sacc1026) supplementation on rumen profile in buffaloes - SINGH, GURPREET; KULKARNI, SHRIKANT; SINGH, RAJVIR (The Indian Journal of Animal Sciences, 2011)
Effect of supplementation of Saccharomyces cerevisiae on microbial population of buffalo calves, was studied. The treated animals were given Yea Sacc1026 @ one bolus (consisting 25 billion live yeast cells)/animalJday for 21 days. The oral supplementation improved the digestine efficiency of ruminants. Â